THE EFFECT OF APPLYING FAIR VALUE ACCOUNTING IN ATTRACTING INVESTORS - Professor. Dr. Rihab Bedoui; Researcher. Ihsan Hammood Habeeb (Scholar Express Journals, 2024)
This research examines the impact of adopting fair value accounting on financial disclosure and investor attraction in the Iraqi market. The study employs both theoretical and empirical approaches, focusing on the positive and negative implications of fair value accounting and its importance in the context of evolving international accounting standards
Keywords: accounting; international; standards; implications